Relationship between pregnant women's combined exposure to heavy metals and their offspring's congenital heart defects in Lanzhou, China - Chen, Lulu; Zhao, Yaqin; Sun, Jianhao; Jiao, Xinjuan; Wu, Zhenzhen; Wang, Jian; Qiu, Jie; Mao, Baohong; Liu, Qing (Frontiers in Pediatrics, 2025)
BackgroundPrevious research has demonstrated that exposure to individual heavy metals elevates the incidence rate of congenital heart defects (CHDs). However, there is a paucity of data concerning the relationship between combined exposure to multiple heavy metals and the occurrence of CHDs. This study seeks to investigate the association between combined heavy metal exposure in pregnant women and the incidence of CHDs in their offspring in Lanzhou, China.MethodsWe conducted a comprehensive review of the birth cohort study undertaken at our hospital from 2010 to 2012, with the objective of investigating the association between combined heavy metal exposure in pregnant women and the incidence of CHDs in their offspring. This analysis was performed utilizing a multifactorial conditional logistic regression model.ResultA nested case-control study was conducted involving 97 case groups and 194 control groups. The median concentrations of nickel (Ni), barium (Ba), lead (Pb), and titanium (Ti) in the blood of pregnant women were measured at 25.58 μg/L, 84.38 μg/L, 69.67 μg/L, and 304.65 μg/L, respectively. The research identified a significant correlation between the concentrations of Ni, Pb, and Ti in the blood of pregnant women and the risk of CHDs (P < 0.05). The optimal cut-off for heavy metals in pregnant women's blood was determined using the ROC curve. Levels below this threshold indicated low exposure, while levels at or above it indicated high exposure. In comparison to low exposure levels, high exposure to nickel (≥189.29 μg/L) in pregnant women was associated with a 2.098-fold increase in the risk of CHDs in their offspring (OR = 3.098, 95% CI: 1.322–7.260). Similarly, high lead exposure (≥86.70 μg/L) resulted in a 1.192-fold increase in the risk of CHDs in offspring (OR = 2.192, 95% CI: 1.021–4.707). Furthermore, high exposure to titanium (≥404.22 μg/L) was linked to a 3.065-fold increase in the risk of CHDs in offspring (OR = 4.065, 95% CI: 1.887–8.758). When compared to low exposure levels, the combined exposure to four heavy metals in the blood of pregnant women is linked to a 4.946-fold increased risk of CHDs in their offspring (OR= 5.946, 95% CI: 2.872–12.309). A significant correlation was observed between Ti exposure levels and the combined exposure levels of four heavy metals in pregnant women, with respect to the risk of isolated CHDs and multiple CHDs (P < 0.05). Additionally, high Ni exposure levels in pregnant women are associated with an increased risk of multiple CHDs (OR 4.321, 95% CI: 1.646–11.348).ConclusionThe cumulative exposure levels of Ni, Ba, Pb, and Ti in the blood of pregnant women are correlated with an elevated risk of CHDs in their offspring.